PENGARUH PRE-HEATING PADA PIROLISIS BIOMASSA LIMBAH AREN TERHADAP CHAR PADA REAKTOR HORIZONTAL MODEL CONTINUOUS - Roli Russiadi; Herman Saputro; Husin Bugis (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
Utilization of palm waste in the form of charcoal briquettes makes the fuel more efficient and in a better form. Thus, charcoal briquette fuel with sugar palm waste is a solution or alternative to solving the waste problem caused by palm trees. This research was conducted with the aim of knowing the effect of pre-heating on the pyrolysis process of palm sugar waste biomass on gas fraction, bio-oil and char. This study used an experimental method conducted in the Mechanical Engineering Education Laboratory of Sebelas Maret University. The research variable is the variation of pre-heating time in the pyrolysis of palm waste biomass against gas fraction, bio-oil and char in a continuous model horizontal reactor. The result of this study is that pre-heating has an effect on the gas fraction. The longer the pre-heating process is carried out, the lower the amount of O2 gas produced. Pre-heating affects the char, so the quality and quantity can be measured.